Effects of Regulatory Support Services on Institutional Review Board Turnaround Times. (July 2017) - Desai, Pankaja; Nasa, Priyanka; Soo, Jackie; Jia, Cunhui; Berbaum, Michael L.; Fischer, James H.; Johnson, Timothy P.
We evaluated how regulatory support services provided by University of Illinois at Chicago's Center for Clinical and Translational Science may reduce Institutional Review Board (IRB) turnaround times. IRB applications were categorized by receipt of any regulatory support and amount of support received. Turnaround time included total turnaround time, time for IRB review, and time for investigators to modify protocols. There were no differences in any turnaround times for supported versus nonsupported applications. However, for supported applications, those receiving more intensive support had total turnaround times 16.0 days ( SE 7.62, p < .05) faster than those receiving less intensive support. Receiving higher regulatory support may be associated with faster approval of IRB submissions.